Manusia dalam Bumi Manusia Pramoedya Ananta Toer - Cholis, Nur; Ma'arif, Muhammad Samsul; Negara, Diah Dwi Ikra (JURNAL AL-AQIDAH, 2024)
Bumi Manusia is a controversial and interesting novel, Pramoedya Ananta Toer as the author was accused of being involved with communists. Bumi Manusia was banned from circulation but then gained a crowded place among readers and has been translated in approximately 36 languages, its ideas and messages will ultimately contribute to the color of the reading public, how to think, behave and exist. This study is a discourse analysis model that aims to describe human existence in Bumi Manusia with the hermeneutic objective method as an analytical approach. The final result can be concluded that humans who exist in Bumi Manusia are none other than those who are armed with knowledge and independence are able to struggle out of various difficulties faced, are able to stand on their own feet, and do not become criminals running away from responsibility. The concept of humanity in Bumi Manusia is rooted in the factual social conditions of the little people and the oppressed. Humans who exist in Bumi Mansusia do not envision perfect humans, or ideal humans who aspire to be, successful winners with achievements based on the ideals of perfect humans who are overwhelmed by perfection, but humans who are able to continue to struggle to get out of the factual tests experienced by humans on earth. Because perfect humans, success and always being winners according to Pramoedya do not exist on earth but in heaven.